Evaluation of magnetite as an indicator mineral for porphyry Cu exploration: a case study using bedrock and stream sediments at the Casino porphyry Cu–Au–Mo deposit, Yukon, Canada. Issue 2 (2022) - McCurdy, Martin W.; Peter, Jan M.; McClenaghan, M. Beth; Gadd, Michael G.; Layton-Matthews, Dan; Leybourne, Matthew I.; Garrett, Robert G.; Petts, Duane C.; Jackson, Simon E.; Casselman, Scott
No abstract available